(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the prevalence of endometriosis in women undergoing surgery of various gynecological indications. METHODOLOGY: This descriptive study included 170 women aged 18–50 years who underwent gynecological surgeries at Liaquat National Hospital from November 2022 to June 2024. Surgeries included hysterectomy, oophorectomy, myomectomy, and laparoscopic adhesiolysis. Endometriosis was identified intraoperatively by the presence of endometrial-like tissue outside the uterus and confirmed histopathologically. Data on demographics, surgical indications, and procedures were analyzed using SPSS version 26.0, with significance set at p < 0.05. RESULTS: The mean age of the participants was noted as 34.44 ± 6.43 years. Among these, endometriosis was observed in 16.5% of cases. Chronic pelvic pain was present in 37.5% of endometriosis cases, while infertility was noted in 15%. Diagnostic laparoscopy (16.3%) and ovarian cystectomy (22.2%) were the most common procedures performed in patients with endometriosis. CONCLUSION: It is to be concluded that women who underwent gynecological surgeries, endometriosis was commonly observed with symptoms such as chronic pelvic pain and infertility. Routine procedures included diagnostic laparoscopy and cystectomy for ovarian cyst. Complete care of patients can only be provided if subclinical endometriosis is also identified and treated by routine laparoscopic evaluation.